Mrs. Pipin Salted Fish Processing Business Development Strategy In The Back Market Village Sibolga City District - Panggabean, Windy Fransiska; Gustiana, Cut; Mahyuddin, Thursina (AGRIBUSINESS JOURNAL, 2023)
The purpose of this research is to analyze internal and external environmental factors that affect the development of the salted fish business in the salted fish processing business of Mrs. Pipin and formulate alternative strategies that can be applied in the business. This research was conducted in the Back market village sibolga city district north sumatera. The method used is a case study method. The determination of the sample in this study is the owner and manager of the salted fish business in the salted fish processing business in the salted fish processing business, Mrs. Pipn in the Back Market Village Sibolga City District North Sumatera. Respondents in the study consisted of 5 key stores. The analysis method used in this study is SWOT and QSPM analysis. The results of the study based on the QSPM analysis obtained the priority of the main strategy in this study is expanding strategic business locations so that good quality products get enough raw materials by collaborating with suppliers in improving the family economy and opening job opportunities for the surrounding community.